A Novel Partitivirus That Confer Hypovirulence to the Plant Pathogenic Fungus Colletotrichum liriopes - Zhu, Jun Zi; Guo, Jun; Hu, Zhao; Zhang, Xu Tong; Li, Xiao Gang; Zhong, Jie (Frontiers in Microbiology, 2021)
Here, we report a novel double-stranded RNA virus designated Colletotrichum liriopes partitivirus 1 (ClPV1) from the plant pathogenic fungus Colletotrichum liriopes. ClPV1 genome has two dsRNAs, named as dsRNA 1 and dsRNA 2, which in the lengths of 1807 and 1706 bp, respectively. The dsRNA 1 and dsRNA 2 encoded proteins showing significant amino acid (aa) sequence identity to the RNA-dependent RNA polymerase (RdRp) and coat protein (CP) of partitiviruses, respectively. Phylogenetic analysis using the aa sequences of RdRp and CP indicated that ClPV1 was grouped to members of the putative Epsilonpartitivirus genus in the Partitiviridae family. Spherical viral particles in approximately 35 nm in diameter and packaging the ClPV1 genome were isolated. Virus elimination and virus transfection with purified viral particles, and biological comparison revealed that ClPV1 could reduce the virulence and conidia production of C. liriopes. To the best of our knowledge, this is the first report of mycovirus in C. liriopes fungus.